2021
DOI: 10.3389/ffgc.2021.684087
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Biennial Burning Has No Adverse Effects on Mature Longleaf Pine Survival or Productivity

Abstract: Emulating natural disturbance has become an increasingly important restoration strategy. In the fire-maintained woodlands of the southeastern United States, contemporary restoration efforts have focused on approximating the historical fire regime by burning at short intervals. Due to concerns over escape and damage to mature trees, most prescribed burning has occurred in the dormant season, which is inconsistent with the historical prevalence of lightning-initiated fire in the region. This discordance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Because of this limitation, we only asked whether prescribed fire resulted in altered growth in the year of burning and refrained from addressing interactions such as those investigated by Ames et al (2015), who found that longleaf pine growth diminished when prescribed fire was applied except during warmer years when growth increased. Typically, juvenile longleaf pines exhibit decreased growth in the year of burning up to 25 years of age (Boyer, 1987; Ford et al, 2010; Haywood & Grelen, 2000) but long‐term studies on mature trees rarely show growth depression in frequently burned stands (e.g., Willis et al, 2021). Our finding of no effect of fire on growth of mature longleaf pines was consistent with these other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this limitation, we only asked whether prescribed fire resulted in altered growth in the year of burning and refrained from addressing interactions such as those investigated by Ames et al (2015), who found that longleaf pine growth diminished when prescribed fire was applied except during warmer years when growth increased. Typically, juvenile longleaf pines exhibit decreased growth in the year of burning up to 25 years of age (Boyer, 1987; Ford et al, 2010; Haywood & Grelen, 2000) but long‐term studies on mature trees rarely show growth depression in frequently burned stands (e.g., Willis et al, 2021). Our finding of no effect of fire on growth of mature longleaf pines was consistent with these other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of P. yunnanensis under natural conditions was approximately 0.93% to 1.27%, while under prescribed burns, it was 1.33%, indicating that P. yunnanensis has some fire resistance and that prescribed burns on it are safe. Furthermore, regular programmed burning was shown to not affect the survival and productivity of mature coniferous forests [48][49][50]. Even after repeated burning over 60 years, there was minimal impact on the structure, composition, or growth of overstory trees [51].…”
Section: Forest Stand Characteristics Of P Yunnanensis Forestmentioning
confidence: 95%